Analytical validation of a psychiatric pharmacogenomic test. (7th February 2018) - Jablonski, Michael R; King, Nina; Wang, Yongbao; Winner, Joel G; Watterson, Lucas R; Gunselman, Sandra; Dechairo, Bryan M
Aim: The aim of this study was to validate the analytical performance of a combinatorial pharmacogenomics test designed to aid in the appropriate medication selection for neuropsychiatric conditions.Materials & methods: Genomic DNA was isolated from buccal swabs. Twelve genes (65 variants/alleles) associated with psychotropic medication metabolism, side effects, and mechanisms of actions were evaluated by bead array, MALDI-TOF mass spectrometry, and/or capillary electrophoresis methods (GeneSight Psychotropic, Assurex Health, Inc.).Results: The combinatorial pharmacogenomics test has a dynamic range of 2.5–20 ng/μl of input genomic DNA, with comparable performance for all assays included in the test. Both the precision and accuracy of the test were >99.9%, with individual gene components between 99.4 and 100%.Conclusion: This study demonstrates that the combinatorial pharmacogenomics test is robust and reproducible, making it suitable for clinical use.